Justification of methodological approaches to assessing the technology transfer readiness - Kozyk, Vasyl; Mrykhina, Oleksandra; Mirkunova, Tamara (Technology audit and production reserves, 2017)
The object of research is methodical approaches to assessing the readiness level of technologies for transfer. One of the most aspects of innovation activity in Ukraine is the lack in the necessary and sufficient number of methodological developments that would determine the readiness level of technology for transfer from universities of business structures. Existing developments are sectoral or local and are fragmentary. In the course of scientific work, a model for assessing the readiness level of technology for transfer is developed, which should provide an understanding of the subject of technology transfer as the relationship between its participants in the creation and transfer of value added in the form of technology. A methodological toolkit is developed to assess the readiness level of technologies for a transfer based on the reliability theory of hierarchically branched systems. Application of the proposed model and methodological tools on the example of the technology of individual passive dosimetry of ionizing radiation shows that the indicator of the mathematical expectation of technology readiness for transfer is 69 %. The obtained indicator indicates the average readiness level of technology for the transfer. The proposed model and methodological tools allow to increase the level of accuracy of the received estimates; establish the nature of the interaction of the elements of the system among themselves and the like.